Die funksionering van Bybelse inhoude in ’n narratief-pastorale gesprek (Afrikaans) - Senekal, Deon Pierre (2013)
The movement from modernism to postmodernism have brought about perceivable changes in contemporary thinking and social practices. An important step was the transition toward the “broader rationalistic” view made in the hermeneutical approach, inclusive of the realization that the collection and accumulation of knowledge is not primarily dependent on sharply formulated methodical rules, but also on the symmetrical interaction between and among equal participants in the communication process. The rise of social-constructionism based on the viewpoint, that the sense and meaning of reality are both reciprocally constructed, did not merely exercise its way and influence on the social sciences but also within the practical theology as a science. In this process the narrative model of counselling mode itself strongly known with the understanding that the story of a person and the particular meaning the person attaches to this story, is that which requires the urgent attention of the pastor. With the realization that several stories are involved in the pastoral occurrences, the question immediately arising is: In what way, does the story of God function in the narrative – pastoral discussion? Could the Story of God make any difference in the pastoral happenings? It was decided to research the role of Biblical contents in the pastoral occurrences by way of the qualitative method. The pastoral behaviour of two co-researchers was researched, this included mutual discussions with them about the use of Biblical contents in their counselling. Certain inferences were made from this discussion, the latter leading to further mutual discussions. In the second instance a focus group was brought into play to reflect on inferences made from individual discussions. Subsequently the researcher interactively related stories from the past (tradition) and modern stories, as well as the inferences from the research, with a view to assess whether a new story would possibly come to the fore. The final chapter concluded with the story in which it was realised, that the meta Story still had an unique and particular role in the pastoral counselling. The religious discourse still retains its primary importance for the pastor as a representative of God. This includes that a pastor cannot detach himself from the accompanying specific identity. Within the framework of thought of the postmodernism we should guard against elevating the meta Story to become the “most important” aspect. The reason for this is that the authoritative completeness of the story does not lie in its proclamation to be the most important aspect but it rather lies in the Story itself and in the omnipresence and involvement of God in this world. The pastor should realise that it is not necessary to bring into play the Word of God, because God’s love and compassion is evident in the demeanour and behaviour of the pastor. The specific and challenging task of the pastor persists, in bringing man into contact with the Story of Jesus of Nazareth. The timing and manner of this “bringing into contact” must be applied with a sense of responsibility. This should lead to additional opportunities in constructive dialogue in which HOPE is established. The Story of God’s hope that brings with it an unparalleled sense and meaning. Those who prefer to negate or omit the meta Story in an attempt to comprehend man and his particular circumstances, is guilty of a major error of reasoning. === Thesis (DPhil (Practical Theology))--University of Pretoria, 2006. === Practical Theology === unrestricted